(untitled) (diségno, 2023)
Images of the city must be compared against a complex organism that changes over time. They can take shape on a sheet of paper or in digital space, but can also become mental images that populate our thinking and condition our perception of the city itself. Each image conveys the Author’s gaze and is received with the observer’s gaze: just as the ability to represent changes depending on the time and place to which the Author belongs, so with the ability to see images. The creation of a digital platform would make it possible to valorize the iconographic heritage belonging to a city: by visualizing the images in a diachronic and synchronic sequence, their communicative register is understood and they are rendered as parts of a unitary story. It is hypothesized that, through the user’s participation in the implementation and interrogation of the platform, it is possible to generate an unprecedented composite figurative text of the city so that, in the manner of the Bilderatlas Mnemosyne, it becomes a tool for thinking through images. Users will contribute to writing a tale, narrated simultaneously from different points of view, which will have as its subject both urban transformations and the evolution of the ideal image that, in the various representations, the city gives of itself. Through a tale thus conceived, the user will become both its Reader and Writer and with new and original mental associations give shape to new stories about the city.